Fungus- (Alternaria sp.) Mediated Silver Nanoparticles Synthesis, Characterization, and Screening of Antifungal Activity against Some Phytopathogens - Theint Theint Win; Sikandar Khan; PengCheng Fu (Journal of Nanotechnology)
The scientific consensus is now on developing a biocontrol agent that can cause cellular metabolic reprogramming against agricultural pathogens. Biosynthesis of silver nanoparticles was performed by using phytopathogenic fungi (Alternaria sp.) isolated from banana cultivated soil. Alternaria sp. can grow very fast and produce high enough bioactive compounds. This study aims to biosynthesize silver nanoparticles (AgNPs) using fungal Alternaria sp.’s metabolites as a safe antifungal agent against plant pathogenic fungi (Fusarium spp. and Alternaria sp.). To visualize the formation of AgNPs, analytical instruments were used, such as ultraviolet-visible (UV-Vis) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, scanning transmission electron microscopy (STEM), energy dispersive X-ray (EDX), and elemental mapping. The UV-visible spectra showed a peak at 435 nm. Analysis of scanning transmission electron microscopy (STEM) micrographs evidenced that the size of synthesized silver nanoparticles ranged between 3 and 10 nm. The resulting AgNPs showed distinct antifungal activity against selected plant pathogenic fungi. Synthesized AgNPs have demonstrated remarkable potential for the use of antifungal compounds to combat plant diseases.